Exploring food system resilience to the global polycrisis in six Asian countries - Favas, Caroline; Cresta, Chiara; Whelan, Elizabeth; Smith, Kristie; Manger, Mari S.; Chandrasenage, Damith; Singhkumarwong, Anusara; Kawasaki, Jintana; Moreno, Susana; Goudet, Sophie (Frontiers in Nutrition, 2024)
The world is currently in the midst of a global food crisis brought about and exacerbated by a series of mutually reinforcing shocks to food systems This study investigated the resilience of food systems in six Asian countries (Bangladesh, Kyrgyz Republic, Lao PDR, Pakistan, Philippines, and Sri Lanka) amidst the global ‘polycrisis’ caused by COVID-19, geopolitical conflicts, and climate change. Trend analyses were performed for 19 indicators sourced from global databases and World Food Programme national data, representing the four domains of food system resilience: exposure to shocks; resilience capacities and agro- and food diversity, resilience responses and strategies; and long-term resilience outcomes. The analysis revealed that all six countries experienced the effects of the ‘polycrisis’, leading to diverse impacts on exchange rates, with Sri Lanka, Pakistan, and Lao PDR facing significant currency depreciation. While most countries increased crop production and decreased food imports during the crisis, government economic support during the pandemic varied widely. Resilience outcomes, including national food price inflation and the proportion of populations facing food insecurity, witnessed upward variations. Overall, countries with higher resilience capacities at the start of the ‘polycrisis’ showed less severe long-term resilience outcomes. Our findings highlight the varied challenges and resilience capacities across each country, influenced by a complex interplay of economic, political, agricultural, and food affordability factors crucial for determining long-term resilience in their food systems. Recommendations for future research include focusing on resilience assessment in food systems, integrating climate change adaptation measures, and developing early intervention strategies.